2013
DOI: 10.1111/dme.12343
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin level is higher in poorly controlled patients with Type 2 diabetes and people without diabetes, aged over 55 years

Abstract: Poorly controlled patients with type 2 diabetes and people without diabetes of over 55 years of age are likely to be at a higher risk of developing hyperferritinaemia. Thus, regular assessments of serum ferritin might be important for those who are at risk of hyperferritnaemia for prevention and an early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In our cross‐sectional study, 70% of individuals with type 2 diabetes had good diabetic control. Women with type 2 diabetes in our study tended to have higher iron stores, in agreement with those studies . Circulating hepcidin and sTfR seem to be more sensitive markers regarding changes in iron status even in well controlled diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our cross‐sectional study, 70% of individuals with type 2 diabetes had good diabetic control. Women with type 2 diabetes in our study tended to have higher iron stores, in agreement with those studies . Circulating hepcidin and sTfR seem to be more sensitive markers regarding changes in iron status even in well controlled diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Although most of the studies have reported higher serum ferritin in type 2 diabetes , Rajpathak et al. did not find this increase , and other authors found an increase in serum ferritin in women but not in men . In fact Batchuluun et al.…”
Section: Discussionmentioning
confidence: 89%
“…Serum ferritin is commonly used as a marker of iron stores, and a negative correlation between serum ferritin and insulin sensitivity has been reported [39]. Further, patients with DM are more prone to high concentrations of ferritin compared to patients without DM [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Further, patients with DM are more prone to high concentrations of ferritin compared to patients without DM [39,40]. This can be explained by the fact that iron metabolism is bidirectional, i.e., as iron affects glucose metabolism and glucose metabolism may also influence iron metabolism [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation